Comparative study of bacteriological profile in infective exacerbation of chronic obstructive pulmonary disease and community-acquired pneumonia - Anindita Menon; B S Nagaraja; Arjun P Chandrashekar (APIK Journal of Internal Medicine, 2023)
Background: Community-acquired pneumonia is a differential diagnosis of acute exacerbation of chronic obstructive pulmonary disease (COPD); further both have similar pathogenic spectra. Both the American Thoracic Society and the European Respiratory Society follow similar empirical antibiotic choices for the two conditions. However, there are some differences in the bacterial spectra between the two conditions, particularly when the severity of the disease differs. In the present study, we want to study the differences in the clinical features, bacteriological spectra, and antibiotic susceptibilities in patients with community-acquired pneumonia versus patients with COPD exacerbation and provide a scientific basis for antibiotic selection. Aims: 1. To analyze the differences in the pathogenic spectra and antibiotic sensitivity profile between COPD exacerbation and community acquired pneumonia. 2. To study the differences in the clinical features and outcomes of the two conditions. Subjects and Methods: The study was a prospective observational study conducted from November 2019 to May 2020 in Bangalore Medical College and Research Institute on 30 patients diagnosed with acute exacerbation of COPD and 30 patients diagnosed with community acquired pneumonia. Detailed history, physical examination, and standard laboratory tests were taken on admission. The presence of new consolidation on chest radiograph was recorded. Sputum specimens collected by expectoration and tracheal suctioning or bronchoalveolar lavage were analyzed by Gram staining and microscopy and also by culture. The isolates were also tested for antibiotic sensitivity. The severity of Chronic obstructive pulmonary disease (COPD) exacerbation was assessed by the DECAF score and the severity of the CAP group was assessed by the Pneumonia Severity Index. The differences between the two groups were analyzed. The progression of the disease and the outcomes were observed. Results: Out of 30 (100%) participants in each group, both pneumonia and COPD participants had higher percentage of male participants; 24 (80%) and 26 (86.7%) participants, respectively. The COPD-exacerbation group was significantly older than the community-acquired pneumonia group (63.20 ± 11.82 vs. 43.73 ± 16.58). Klebsiella pneumoniae, Pseudomonas, Streptococcus pneumoniae, and Escherichia Coli were the most commonly isolated species in COPD subjects, whereas S. pneumoniae, Staphylococcus aureus, Haemophilus influenzae, and other organisms were more commonly isolated from pneumonia participants. The drug-resistance rates of S. pneumoniae to penicillin, macrolide and quinolone antibiotics commonly used empirically to treat community acquired pneumonia was 52.6%, 79% and 79% respectively. The sensitivity of Pseudomonas to Carbapenems was 50% and to fluoroquinolones was 16.7% while all the strains were found to be resistant to Aminoglycosides, Penicillin, Cephalosporins, and Macrolides. Conclusions: In our study, we found that K. pneumoniae was the most common pathogen in patients with an exacerbation of COPD while S. pneumoniae was the most common pathogen in patients with community acquired pneumonia. In our study the organisms responsible for community acquired pneumonia were largely resistant to penicillins, macrolides, and tetracyclines, which are the antibiotics of choice for empirical treatment. Similarly, in patients with exacerbation of COPD, the organisms isolated had a far greater degree of resistance to the above-mentioned antibiotics than that seen in our patients with pneumonia. We conclude that antibiotic regimens should be culture driven rather than empirical to be effective while also countering drug resistance.